(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This work is about the focus of differentiation, which must be aware of all the ways students are different from one another, and to plan to teach in ways that capitalize on those differences.